Lactobacillus reuteri Reduces the Severity of Experimental Autoimmune Encephalomyelitis in Mice by Modulating Gut Microbiota - He, Baokun; Hoang, Thomas K.; Tian, Xiangjun; Taylor, Christopher M.; Blanchard, Eugene; Luo, Meng; Bhattacharjee, Meenakshi B.; Freeborn, Jasmin; Park, Sinyoung; Couturier, Jacob; Lindsey, John William; Tran, Dat Q.; et al. (Frontiers in Immunology, 2019)
The gut microbiome plays an important role in immune function and has been implicated in multiple sclerosis (MS). However, how and if the modulation of microbiota can prevent or treat MS remain largely unknown. In this study, we showed that probiotic Lactobacillus reuteri DSM 17938 (L. reuteri) ameliorated the development of murine experimental autoimmune encephalomyelitis (EAE), a widely used animal model of MS, a model which is primarily mediated by TH17 and TH1 cells. We discovered that L. reuteri treatment reduced TH1/TH17 cells and their associated cytokines IFN-γ/IL-17 in EAE mice. We also showed that the loss of diversity of gut microbiota induced by EAE was largely restored by L. reuteri treatment. Taxonomy-based analysis of gut microbiota showed that three “beneficial” genera Bifidobacterium, Prevotella, and Lactobacillus were negatively correlated with EAE clinical severity, whereas the genera Anaeroplasma, Rikenellaceae, and Clostridium were positively correlated with disease severity. Notably, L. reuteri treatment coordinately altered the relative abundance of these EAE-associated taxa. In conclusion, probiotic L. reuteri changed gut microbiota to modulate immune responses in EAE, making it a novel candidate in future studies to modify the severity of MS